PENGARUH MANAJEMEN KONFLIK DAN STRESS KERJA TERHADAP KINERJA KARYAWAN PADA PT HALUAN KEPRI BATAM - Hutagalung, Grace; Herman, Hendri (SCIENTIA JOURNAL, 2019)
PT Haluan Kepri is a media company engaged in newspapers. PT Haluan Kepri always strives to improve employee performance. In this effort, it was found that there were still problems occurring within the company. Conflict Management and Job Stress are the problems facing this company. Wirawan defines conflict management as the process of parties involved in conflict and developing conflict strategies to control conflict to produce the desired resolution. And Hasibuan defines stress as a condition of tension that affects one's emotions, thought processes, and conditions. This research was conducted to determine the effect of conflict management and stress work performed by the company on employee performance. This research was conducted on employees of PT Haluan Kepri Batam and the number of samples was determined by 125 respondents using the Slovin formula. Based on the results of multiple regression studies, the following equation is obtained: Y =14,591+0,330X1+0,284X2. From the results of this study, it was concluded that conflict management has a positive and significant influence on employee performance. Job stress has a positive and significant effect on employee performance. And conflict management and stress work together have a positive and significant influence on employee performance at PT Haluan Kepri Batam.